Electron stimulated desorption from condensed benzene - Álvarez, L. (2024)
Funding Information: This study has partially been supported by the Spanish Ministry of Science and Innovation (Project PID2019-104727RB-C21), A. G. A. and L. A. thank MICIU and the local CAM government, respectively, for their corresponding grants within the “Garantía Juvenil” programmes. A. I. L. and P. L. V. acknowledge the Portuguese National Funding Agency (FCT) through research Grants CEFITEC (UIDB/00068/2020). The experiments were supported by the Natural Science and Engineering Research Council of Canada (RGPIN-2018-14882). Publisher Copyright: © 2024 The Royal Society of Chemistry.